2000
DOI: 10.1093/ptr/10.4.450
|View full text |Cite
|
Sign up to set email alerts
|

Developing Methods to Study Child Psychotherapy Using New Scales of Therapeutic Alliance and Progressiveness

Abstract: The purpose of this study was to adapt a methodology, which has previously been successfully employed in adult psychotherapy research, to study videotaped play therapy sessions with children. Therapist interventions in a child psychotherapy case were rated for Plan-compatibility, a case-specific measure of predicted helpfulness based on an independently generated case formulation. Independent judges rated patient material before and after each intervention with the Progressiveness Scale for Children, a generic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
1
15
0
1
Order By: Relevance
“…Although no quality measure of Rogers's () conditions exists for children, some child measures do address the therapeutic alliance. For example, the Child Therapeutic Alliance Scale (Grienenberger & Foreman, 1993, as cited in Foreman, Gibbins, Grienenberger, & Berry, ) is an eight‐item observational scale. As such, it does not measure the child's subjective experience.…”
Section: Child‐centered Play Therapymentioning
confidence: 99%
“…Although no quality measure of Rogers's () conditions exists for children, some child measures do address the therapeutic alliance. For example, the Child Therapeutic Alliance Scale (Grienenberger & Foreman, 1993, as cited in Foreman, Gibbins, Grienenberger, & Berry, ) is an eight‐item observational scale. As such, it does not measure the child's subjective experience.…”
Section: Child‐centered Play Therapymentioning
confidence: 99%
“…The results of the research studies in turn shaped subsequent clinical discoveries and theoretical elaboration'' (Silberschatz, 2005, p. 189). Research has been carried out demonstrating that the client's plan can be reliably formulated for a psychoanalysis (Caston, 1986), for brief (16 session) adult therapies (Curtis & Silberschatz, 1997), and for child therapy (Foreman, Gibbins, Grienenberger, & Berry, 2000). The concept of testing has also been studied empirically, the ability of raters to identify tests in an analytic transcript as well as the effects of passed and failed tests.…”
Section: Smith College Studies In Social Workmentioning
confidence: 99%
“…Numerous research studies (e.g., Curtis & Silberschatz, 2007;Curtis et al, 1994;Curtis, Silberschatz, Sampson, Weiss, & Rosenberg, 1988;Foreman et al, 2000;Horowitz et al, 1975;Silberschatz, 1986Silberschatz, , 2005Silberschatz, , 2017Silberschatz & Curtis, 1993;Silberschatz, Curtis, & Nathans, 1989) have shown that when the therapist's behavior, communications, and interpretations support the patient's plan (are proplan), the patient improves and the therapy progresses.…”
Section: Cmt: a Brief Introductionmentioning
confidence: 99%